Buckwheat, Fagopyrum esculentus Moench - Campbell, C.G.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
Following a general account of the crop, including importance and distribution, physiology, diseases, genetics and breeding, and the need for unconventional breeding methods, information is reviewed on in vitro methods, including the composition of culture media, establishment of callus culture, organogenesis, plant regeneration and transfer, culture of apical buds, protoplast culture, genetic stability in callus and plants, and biochemical studies using in vitro systems. (Abstract © CAB ABSTRACTS, CAB International)